George Armstrong Custer letter and order - Custer, George A. (George Armstrong), 1839-1876.
Letter and order.
In part, positive and negative photocopies.
Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Army officers